KEMAMPUAN AWAL LITERASI NUMERASI SISWA KELAS V SEKOLAH DASAR DI KOTA TUBAN - Ifa Seftia Rakhma Widiyanti; Mu’jizatin Fadiana; Sri Cacik (Elementeris : Jurnal Ilmiah Pendidikan Dasar Islam, 2023)
This study aims to determine the initial numeracy skills of fifth grade students at Tuban. The research subjects were 32 students in class V SD Negeri Kebonsari I and 35 students in class V SD Negeri Kutorejo III. This research is a quantitative descriptive research based on observation and student scores in working numeracy-based questions. The questions given were 10 questions which included multiple choice, true-false, essay, and matchmaking questions. The readings used in the questions are based on local wisdom in Tuban, so it is hoped that students will find it easier to understand. Based on the test results, it was obtained that the average numeracy score of SD Negeri Kebonsari I students was 51 or in the medium category, and SD Negeri Kutorejo III was 14 or in the low category. These results indicate that the numeracy skills of fifth grade elementary school students in Tuban still need to be improved. Therefore, researchers developed thematic books based on local wisdom to improve the numeracy skills of fifth grade elementary school students.